Oil Frying Processes and Alternative Flour Coatings: Physicochemical, Nutritional, and Sensory Parameters of Meat Products - Luzia Ellen de Mendonça Lima; Bruna Leal Lima Maciel; Thaís Souza Passos (Foods, 2024)
The frying process changes can be desirable and undesirable, involving the physicochemical, nutritional, and sensory aspects, depending on the food and oil properties and the frying process. In this context, alternative flours emerge as a strategy for adding value to the food since they are rich in fiber, vitamins, and minerals, contributing to the variability of ingredients and the full use of food, including residues such as seeds and husks. This narrative review aims to gather current scientific data addressing the alternative flour coatings on breaded meat, mainly chicken, products to evaluate the effects on fried products’ nutritional value, physicochemical parameters, and sensory attributes. Scopus, Science Direct, Springer, and Web of Science search bases were used. This review showed that alternative flours (from cereals, legumes, fruits, and vegetables) used as coatings increase water retention and reduce oil absorption during frying, increase fibers and micronutrient content, which are not present in sufficient quantities in commonly used flours due to the refining process. These flours also reduce gluten consumption by sensitive individuals in addition to favoring the development of desirable sensory characteristics to attract consumers. Therefore, frying processes in oil promote a reduction in humidity, an increase in oil absorption and energy content, and a decrease in vitamin content. In this context, coatings based on alternative flours can reduce these adverse effects of the frying process.